Environmental Molecular Effect on the Macroscale Friction Behaviors of Graphene - Li, Panpan; Wang, Bo; Ji, Li; Li, Hongxuan; Chen, Lei; Liu, Xiaohong; Zhou, Huidi; Chen, Jianmin (Frontiers in Chemistry, 2021)
This study investigated the friction behavior of graphene in air and nitrogen atmosphere environments. The microstructural evolution caused by the variation of atmosphere environments and its effect on the friction coefficient of the graphene is explored. It is demonstrated that graphene can exhibit excellent lubricating properties both in air and nitrogen atmosphere environments. In air, a highly ordered layer-by-layer slip structure can be formed at the sliding interface. Oxygen and H2O molecules can make edge dangling bonds and defects passive. Thus the interaction between the nanosheets and the layers of nanosheets is weak and the friction coefficient is low (0.06–0.07). While the friction coefficient increases to 0.14–0.15 in a nitrogen atmosphere due to the interaction of defects generated in the sliding process, the nitrogen molecules with lone pair electrons can only make the nanosheets passive to a certain degree, thus the ordered slip structure is destroyed and friction is higher. This work reveals the influence of environmental molecules on the macroscale tribological performances of graphene and its effect on the microstructure at the sliding interface, which could shed light on the lubricating performance of graphene in environmental atmospheres and help us to understand the tribological behaviors of graphite at the macroscale.